Adipose tissue IL-23 is associated with fasting blood glucose and HbA1c in overweight/obese individuals - Kochumon, Shihab; Bahman, Fatemah; Albeloushi, Shaima; Al Madhoun, Ashraf; Alzaid, Fawaz; Tuomilehto, Jaakko; Al-Mulla, Fahd; Ahmad, Rasheed (Frontiers in Endocrinology, 2025)
IL-23, a proinflammatory cytokine, plays a role in the development of inflammatory diseases. However, the association between IL-23 expression in adipose tissue (AT) and glycemic changes in obesity remains unclear. This cross-sectional study aimed to examine the relationship of adipose tissue IL-23 (AT-IL-23) expression with other inflammatory mediators within the same compartment and insulin resistance markers fasting blood glucose (FBG) and glycated hemoglobin (HbA1c) in overweight/obese individuals. Fat biopsies were collected from 10 individuals with a body mass index (BMI) < 25kg/m2 and 51 individuals with a BMI > 25kg/m2 and were analyzed for IL-23 and other inflammatory markers using qRT-PCR. Inflammatory markers, including CD16, CD11c, CCR2, CCR5, TNF-α, IL-1β, IL-2, IL-12, CCL8, CCL19, and CXCL9, were positively correlated with IL-23 in the AT-compartment in the obesity context. Notably, AT-IL-23 was correlated positively with FBG, HbA1c, and homeostasis model assessment of insulin resistance (HOMA-IR), while negatively correlating with adiponectin. These findings suggest that AT-IL-23 is associated with metabolic inflammation and insulin resistance in obesity, suggesting it may be of interest for future biomarker studies.